Blood glucose concentrations and progression of diabetic retinopathy: the seven year results of the Oslo study. Issue 6818 (4th January 1992) - Brinchmann-Hansen, O.; Dahl-Jørgensen, K.; Sandvik, L.; Hanssen, K. F.
Abstract : OBJECTIVE--To study insulin dependent diabetic patients for change in non-proliferative retinopathy and its relation to glycaemic control and to various clinical background data. DESIGN--Prospective study with follow up for seven years. SETTING--Outpatient departments of university hospitals. MAIN OUTCOME MEASURES--Glycated haemoglobin concentration; degree of retinopathy. RESULTS--Retinopathy worsened by an overall increase in counts of microaneurysms and haemorrhages from 17 (SD 25) to 45 (58) (p = 0.005). Intensified insulin treatment and home blood glucose monitoring improved concentrations of glycated haemoglobin (HbA1) from 11.2% (2.2%) at the start of the study to a mean of 9.5% (1.5%) over the seven years of the study (p less than 0.0001). A mean value for HbA1 greater than 10% was associated with an increased risk of progression of retinopathy and a mean value less than 8.7% was associated with a diminished risk. Multiple regression analysis identified four independent variables as indicative of outcome of retinopathy after seven years: HbA1 value at baseline; the change in HbA1 from start to the mean level through the seven years; duration of diabetes; and retinopathy at start. Age, blood pressure, and urinary albumin excretion were not related to the presence or progression of retinopathy. CONCLUSION--Secondary intervention by long term lowering of glycated haemoglobin has a beneficial impact on non-proliferative retinopathy. A four factor regression model can determine patients at high risk of severe retinopathy.